Highly efficient non-doped blue fluorescent OLEDs with low efficiency roll-off based on hybridized local and charge transfer excited state emitters. Issue 19 (5th May 2020) - Lv, Xianhao; Sun, Mizhen; Xu, Lei; Wang, Runzhe; Zhou, Huayi; Pan, Yuyu; Zhang, Shitong; Sun, Qikun; Xue, Shanfeng; Yang, Wenjun
Abstract : A new pure fluorescent blue HLCT-emitter was designed and synthesized. Highly efficient non-doped blue OLEDs with low efficiency roll-off were achieved. Abstract : Designing a donor–acceptor (D–A) molecule with a hybridized local and charge transfer (HLCT) excited state is a very effective strategy for producing an organic light-emitting diode (OLED) with a high exciton utilization efficiency and external quantum efficiency. Herein, a novel twisting D–π–A fluorescent molecule (triphenylamine–anthracene–phenanthroimidazole; TPAAnPI) is designed and synthesized. The excited state properties of the TPAAnPI investigated through photophysical experiments and density functional theory (DFT) analysis reveal that its fluorescence is due to the HLCT excited state. The optimized non-doped blue OLED using TPAAnPI as a light-emitting layer exhibits a novel blue emission with an electroluminescence (EL) peak at 470 nm, corresponding to the Commission International de L'Eclairage (CIE) coordinates of (0.15, 0.22). A fabricated device termed Device II exhibits a maximum current efficiency of 18.09 cd A −1, power efficiency of 12.35 lm W −1, luminescence of ≈29 900 cd cm −2, and external quantum efficiency (EQE) of 11.47%, corresponding to a high exciton utilization efficiency of 91%. Its EQE remains as high as 9.70% at a luminescence of 1000 cd m −2 with a low efficiency roll-off of 15%. These results are among the best for HLCT blue-emitting materials involved in non-doped blue fluorescent OLEDs. The performance of Device II highlights a great industrial application potential for the TPAAnPI molecule.